Behind the Caregiving Role—Compassion Fatigue Among Family Caregivers in Palliative Care - Ulviye Ozcan Yuce; Nilay Bektas Akpinar (Journal of Hospice & Palliative Nursing, 2026)
This study aimed to explore the experiences and perceptions of family caregivers of patients receiving treatment in the palliative care unit of a public hospital due to various chronic illnesses, with a particular focus on compassion fatigue. A qualitative descriptive design informed by an interpretivist perspective was employed. Twelve family caregivers were recruited, and face-to-face, individual interviews were conducted. Data were collected through open-ended questions using a semi-structured interview guide. The analysis revealed 5 overarching themes: perceived emotional impacts of compassion fatigue, direct experiences related to compassion fatigue, life domains compromised because of caregiving responsibilities, strategies for maintaining meaningful personal time, and acceptance of the caregiving situation. The findings highlight the necessity of recognizing compassion fatigue at an early stage to minimize its adverse effects on both caregivers and patients. Supporting caregivers’ well-being helps protect their health and sustain quality palliative care.